A comparative multidimensional study of the English translation of Lunyu (The Analects): a corpus-based analysis - He, Mengyu (Penerbit Universiti Kebangsaan Malaysia, 2017)
Although Lunyu (The Analects) is well-known and often mentioned in Confucian scholarship, there have been no focused examinations of the comprehensive linguistic features of its English translations. This study seeks to report a comparative multidimensional investigation into the similarities and differences in the lexico-grammatical features of Lunyu (The Analects) translated by James Legge and Ku Hungming. The comparison is made along five functional dimensions (involved versus informational production, narrative versus nonnarrative concerns, explicit versus situation-dependent reference, overt expression of persuasion, and abstract versus non-abstract information), and the prominent lexicogrammatical features (based on a 67-item feature set) in the two texts are singled out. It is found that there are more private verbs, present tense verbs, be as main verb, past tense verbs, third-person pronouns, and public verbs in Legge’s The Analects of Confucius, whereas Ku’s The Discourses and Sayings of Confucius uses nouns, adjectives, long words, nominalisations, and time adverbials more often. The identified differences in lexico-grammatical patterns are related to the distinct goals of the two translators. The results demonstrate that the multidimensional (MD) approach is effective in differentiating the linguistic features of the two translation versions and motivating a micro-analysis of the texts, seeking to discern the translators’ underlying assumptions about the relations of Confucius and his followers. It is considered that these findings may have implications for the understanding of the translations of The Analects.